Decentralization and Public Politics: the public and the private sectors in education - Vicente Rodriguez (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
This article analyzes the process of decentralization of the Brazilian education and the new institutional configurations assumed in the relations between the public sector and the private sector in offer of educational services. In the new decentralized contexts of the educational politics, the understanding of the actions politics undertaken for the public sector and the private sector is that it will allow to argue the routes of the public politics of education for the country. The analysis of the municipalization of the education in the Metropolitan Region of Campinas and the growth of the private sector constitutes the concerns of this article.